Developing a toolbox of Tier I tests to assess pesticides toxicity on the asymbiotic and symbiotic phases of arbuscular mycorrhizal fungi - Christos Papadopoulos; Marjan Roshanfekrrad; Daniela Tsikou; Kalliope K. Papadopoulou; Maryline Calonne-Salmon; Stephan Declerck; Dimitrios G. Karpouzas (Ecotoxicology and Environmental Safety)
Soil microorganisms are a key protection goal in the European Union (EU) pesticide regulatory framework. Arbuscular mycorrhizal fungi (AMF) were identified as good proxies for assessing pesticides toxicity on the soil microbiota. This could involve ecotoxicity testing at the different life stages of AMF. We evaluated the effects of five pesticides (pyraclostrobin, fludioxonil, hymexazol, etridiazole, glyphosate) and a transformation product (AMPA), with distinct mode of action, on the development and functionality of Rhizophagus irregularis at the asymbiotic and symbiotic phase using a spore germination assay and a gnotobiotic AMF-host plant system (AMF-sandwich test), respectively. Based on arbuscular colonization in the AMF-sandwich test, fludioxonil was the most toxic (EC50 0.085 mg/L) followed by glyphosate (EC50 2.58 mg/L) and pyraclostrobin (EC50 9.22 mg/L), while etridiazole, hymexazol, and AMPA showed EC50 values higher than the highest tested concentration. However, for glyphosate and pyraclostrobin negative effects on symbiosis functioning were observed at lower concentrations than for colonization, as depicted by the expression of plant marker genes and/or P-uptake, suggesting the establishment of non-functional arbuscular symbiosis. The high toxicity of fludioxonil (EC50 0.03 mg/L) and the low toxicity of AMPA (EC50 > 432 mg/L) on R. irregularis was verified also for the asymbiotic phase via spore germination assay. Comparative tests showed differences in the toxicity of pure active substances and commercial formulations of fludioxonil and pyraclostrobin on the AMF-sandwich test. We propose that the AMF-sandwich system together with the spore germination test could be used as a toolbox for Tier-I assessment of pesticides toxicity on AMF.